THE ROLE OF FAITH AND KNOWLEDGE IN THE PROCESS OF PERSONALITY FORMATION: THROUGH THE PRISM OF THE VIEWS OF PATRIARCH JOSYP SLIPYI - ZVARYCH, Ganna; REBUKHA, Liliia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
The article analyzes the role of faith and knowledge in the process of personality formation, which is connected with the educational activity of the person, and, therefore, with the formed spiritual competencies. It has been proven that educational institutions serve as an influential centre of culture and can generate a complete personality with specific value orientations for becoming a worthy citizen of modern society. The importance of faith and knowledge, which influence the formation of a humanistically oriented, comprehensively developed personality, is outlined. Today, religious education is the basis of morality. Accordingly, both Church leaders and outstanding Ukrainian scientists-pedagogues contributed to moral education, which helped to create Ukrainian Christian pedagogy. The significant contribution of Patriarch Yosyp Slipyi to the development of the spiritual education of the Ukrainian people, which contributes to the Christian upbringing of excellent and honest citizens for society, has been traced. It has been proven that faith is a sufficiently subtle spiritual world of subjective experiences, aspirations and religious ideas; it is present in science and scientific creativity, in art and everyday life. Faith inspires everyone to know higher spiritual and moral values; therefore, deep immersion in knowledge in this area is essential in strengthening faith. Patriarch Yosyp Slipyi convincingly proves, based on knowledge, that without faith, everyday life has no meaning since a person is born with the need for faith, lives with it and develops it in himself. Each of us is a bearer of faith and shares this quality with others, forming an effective field of spiritual communication. It is substantiated that knowledge serves as a carrier of great spiritual and valuable potential, where the formation of worldview positions of a young person directly depends on the content of educational disciplines. Therefore, without faith in the power of knowledge, it isn't easy to know oneself and the environment. It was concluded that faith shapes an individual's worldview, and his aspirations enable self-realization. For an individual, faith gives life force, causes access to human existence, and serves as the main prerequisite for entering a modern person into a new integrated system of values, which society invests in the basis of education. Currently, the fact that in the contemporary paradigm of humanization and humanitarianization of education, the phenomenon of faith acquires the status of a powerful tool in the formation of a socially oriented, comprehensively harmonious personality is being observed.